Single stage laparoscopic cholecystectomy with intraoperative endoscopic retrograde cholangiopancreatography for cholecysto-choledocholithiasis. Lesson learnt from the COVID-19 pandemic - Gerosa, Martino; Guttadauro, Angelo; Stillittano, Domenico Francesco; Sassun, Richard; Sileo, Annaclara; Vignati, Barbara; Di Fratta, Emanuele; Maggioni, Dario; Mari, Giulio (Frontiers in Surgery, 2024)
Introduction: Choledocholithiasis, a common complication of gallstone disease, poses significant risks including cholangitis and pancreatitis. Various treatment approaches exist, including single-stage and two-stage techniques, with recent literature suggesting advantages of the single-stage approach in terms of outcomes and cost-effectiveness. This study evaluates the feasibility, efficacy, and safety of single-stage laparoscopic cholecystectomy combined with intraoperative endoscopic retrograde cholangiopancreatography (LC + iERCP) compared to the previously adopted two-stage approach. Methods: A retrospective analysis was conducted on patients undergoing single-stage LC + iERCP for cholecysto-choledocholithiasis during the COVID-19 pandemic (2020-2022). Data on de-mographics, preoperative assessments, intraoperative parameters, and postoperative outcomes were collected and compared with an historical control group undergoing the two-stage approach (LC + preopERCP). Hospitalization costs were also compared between the two groups. Results: A total of 190 patients were included, with 105 undergoing single-stage LC + iERCP. The single-stage approach demonstrated successful completion without cystic duct cannulation, with no conversions to open surgery. Operative time was comparable to the two-stage approach, while hospital stay, and costs were significantly lower in the single-stage group. Complication rates were similar between the groups. Conclusions: Single-stage LC + iERCP appears to be a feasible, effective, and safe approach for treating cholecysto-choledocholithiasis, offering potential benefits in terms of reduced hospital stay, OR occupation time, and costs compared to the two-stage approach. Integration of this ap-proach into clinical practice warrants consideration, unless there are logistical challenges that cannot be overcome or lack of endoscopic expertise also for treating challenging urgent cases.